Developing and Assessing an Integrated Comprehensive Obstetric Ultrasound Training Program for Undergraduate Medical Students – the Fetal Assessment in Medical Education Study (FAME study) - Matschl, Julia; Plöger, Ruben; Wittek, Agnes; Walter, Adeline; Gembruch, Ulrich; Strizek, Brigitte; Recker, Florian (Geburtshilfe und Frauenheilkunde, 2025)
This study aimed to evaluate the effectiveness of a prenatal ultrasound course for medical students, focusing on enhancing competencies in fetal sonography through the integration of theoretical knowledge and hands-on practice.This was a longitudinal study conducted over the winter semester of 2023/24.Study took place in a medical education setting, with practical sessions conducted in a clinical environment and theoretical instruction.Twenty medical students participated in the course.The course was taught by expert faculty and included practical training with live models in real-life conditions, supplemented by online video lectures. The study used Objective Structured Clinical Examinations administered before and after the course, along with multiple-choice questionnaires following each of the six course modules, to assess learning outcomes. Learning success was measured using pre- and post-course OSCE results and MCQ scores. Statistical analysis was performed using the Wilcoxon signed-rank test for OSCE scores and the Spearman correlation test to examine relationships between MCQ results and practical skills.Primary outcomes included the change in OSCE scores and the correlation between MCQ scores and practical skills.Median OSCE scores improved from 18.94% pre-course to 95.45% post-course, indicating significant enhancement in practical skills. However, no significant correlation was found between MCQ and post-course OSCE scores. Students expressed high satisfaction with the course.The study demonstrates effectiveness of a practice-oriented educational approach in improving medical students’ competencies in fetal sonography, providing valuable insights for optimizing future medical curricula in prenatal imaging.
Keywords: ultrasound; training; medical students; ultrasound education; prenatal training